INCREASING STUDENT LEARNING OUTCOMES MATERIAL THREE VARIABLE LINEAR EQUATIONS THROUGH IMPLEMENTATION OF PROBLEM SOLVING MODEL IN CLASS X MIPA 1 SMA NEGERI 1 MOJOSARI - Sulami Sulami (Jurnal Scientia, 2022)
The purpose of this study was to determine the increase in student learning outcomes in class X MIPA 1 SMA Negeri 1 Mojosari, Mojokerto Regency through the application of problem solving models to the material of three variable linear equations. This research is a classroom action research with 2 cycles of improvement which includes the stages of planning, implementing, observing and reflecting. The action given is to apply the problem solving model to the three-variable linear equation material. The research was carried out from August to September 2019 in class X MIPA 1 SMA Negeri 1 Mojosari. The results showed that (1) the implementation of lesson plans showed that lesson plans could be implemented well and increased from an average score of 2.77 (good) in the first cycle to 3.31 (good) in the second cycle (2) student activity showed student centered learning ) with an activity percentage of 86.27% in the first cycle increased to 93.62% in the second cycle and students were very enthusiastic about listening to the information conveyed by the teacher, (3) Student responses after the application of the problem solving model used showed a positive response, and (4) Completeness of learning outcomes in cycle I individually it has been achieved and classically it has not been achieved, while in cycle II completeness of learning outcomes both individually and classically has been achieved. Mastery learning outcomes achieved in the second cycle, increased from 77.77% in the first cycle to 91.66% in the second cycle.